Sentinel lymph node detection by means of indocyanine green using the Karl Storz VITOM® fluorescence camera: a comparison between primary sentinel lymph node biopsy versus sentinel lymph node biopsy after neoadjuvant chemotherapy - Staubach, Petronilla; Scharl, Anton; Ignatov, Atanas; Ortmann, Olaf; Inwald, Elisabeth C.; Hildebrandt, Thomas; Gerken, Michael; Klinkhammer-Schalke, Monika; Scharl, Sophia; Papathemelis, Thomas (Journal of Cancer Research and Clinical Oncology, 2020)
Purpose: The usage of radioactive Technetium99m (Tc99m) colloid for the purpose of sentinel lymph node biopsy (SLNB) in early breast cancer is considered the gold standard in Germany. However, new tracers, such as near-infrared (NIR) imaging agents like indocyanine green (ICG) could offer an alternative in future, as they overcome drawbacks associated with radioactive Technetium99m (Tc99m) like limited availability, high costs and radioactivity exposure for both patients and surgeons. Methods: In this double-arm retrospective study, we sought to establish the usefulness of indocyanine green as an alternative or an addition to the conventional Technetium99m (Tc99m) in the identification of the SLN in early breast cancer. Results: Among the 161 patients who underwent primary SLNB, 34 patients had at least 1 SLN with metastasis. Among these patients with SLN metastasis, 33 had the SLN detected by ICG; while 31 had the SLN detected by Tc99m. The conventional Technetium99m radiotracer failed to detect 2 patients with metastasis in this Arm of the study. Among the 87 patients who underwent SLNB after NACT, 13 patients had at least 1 SLN with metastasis. Among these 13 patients with SLN metastasis, ICG and Tc99m had detected the SLN among 12 patients, while 1 patient had been detected by ICG alone. Conclusions: Our results show that ICG is as effective as the radioisotope for SLNB even among patients who have undergone NACT. This trial is registered with the German Clinical Trial Register, ID: DRKS00013606.
CRIS-Team Scopus Importer:2020-12-04
Keywords: Breast cancer; Indocyanine green; Neoadjuvant therapy; Sentinel biopsy